Synthesis of DNA-encoded screening libraries - Kamdem, Olivia (Technische Universität Dortmund, 2017)
The discovery of small organic molecules capable of binding to specific biological targets represents a decisive step towards the development of novel therapies for the treatment of human diseases. However, identifying such small bioactive molecules is often a complex process involving numerous challenges, including low-affinity binding to target proteins. This necessitates the development of effective and powerful strategies to generate large sets of chemical compound libraries and novel screening methodologies to identify binding molecules. High throughput screening (HTS) has proven to be a powerful tool in facilitating the screening of large compound collections against disease-related protein targets. However, HTS has many requirements that must be fulfilled, including: miniaturized and compatible assay formats, an infrastructure with a high degree of automatization, large-scale data analysis, and trained staff. Owing to these significant technical and financial requirements, new technologies to facilitate ligand discovery that can be implemented in the academic sphere are highly desirable. In this regard, technologies based on DNA encoded chemical libraries (DELs) offer a considerable advantage over conventional HTS technologies as they are rapid, cost-effective, and employ user-friendly screening logistics. Two points in particular make the screening of DNA-encoded libraries attractive. Firstly, large numbers of compounds can be pooled and screened, so that a dedicated infrastructure for handling of compound libraries is unnecessary. Moreover, only one assay format is required for all protein targets facilitating assay development. Hits emerging from the selection assay must be validated in additional assays and may serve as lead compounds for further development towards probes or even therapeutic agents.
Synthese von DNA-kodierten Screening Substanzbibliotheken
Keywords: DEL; DNA; TIDEC; tiDEL; 570; 540